Modern wireless communications - Haykin, Simon S. 1931- (Pearson/Prentice Hall, 2005)
Intended for use in undergraduate courses, this textbook discusses the techniques of wireless communications according to the evolution of spectral utilization of the radio channel. Chapters discuss topics like propagation and noise, modulation and frequency-division multiple access, coding and time